Biblical Aramaic and related dialects: an introduction - Cook, Edward M. (Cambridge University Press, 2022)
Biblical Aramaic and Related Dialects is a comprehensive, introductory-level textbook for the acquisition of the language of the Old Testament and related dialects that were in use from the last few centuries BCE. Based on the latest research, it uses a method that guides students into knowledge of the language inductively, with selections taken from the Bible, the Dead Sea Scrolls, and papyrus discoveries from ancient Egypt. The volume offers a comprehensive view of ancient Aramaic that enables students to progress to advanced levels with a solid grounding in historical grammar. Most up-to-date description of Aramaic in light of modern discoveries and methods. Provides more detail than previous textbooks. Includes comprehensive description of Biblical dialect, along with Aramaic of the Persian period and of the Dead Sea Scrolls. Guided readings begin with primary sources, enabling students learn the language by reading historical texts.